2020
DOI: 10.1111/papt.12277
|View full text |Cite
|
Sign up to set email alerts
|

Pilot service evaluation of a brief psychological therapy for self‐harm in an emergency department: Hospital Outpatient Psychotherapy Engagement Service

Abstract: Background Brief psychological therapies may be helpful for people who have recently self‐harmed. The current paper reports on a service evaluation of a novel brief therapy service based within an Emergency Department, Hospital Outpatient Psychotherapy Engagement (HOPE) Service. This service combines elements of psychodynamic interpersonal and cognitive analytic therapy to help people who present with self‐harm‐related difficulties. The primary aim of this service evaluation was to ascertain the feasibility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Research into CAT so far provides evidence for the feasibility, acceptability, and safety of this approach across a variety of settings, populations, and modalities (Chanen et al ., 2008; Evans, Kellett, Heyland, Hall, & Majid, 2017; Gleeson et al ., 2012; Hallam et al ., 2020; Taylor, Fien, et al, 2020; Taylor et al ., 2018). Where research is currently less clear is with regard to the efficacy of CAT.…”
Section: The Current Landscape Of Cat Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Research into CAT so far provides evidence for the feasibility, acceptability, and safety of this approach across a variety of settings, populations, and modalities (Chanen et al ., 2008; Evans, Kellett, Heyland, Hall, & Majid, 2017; Gleeson et al ., 2012; Hallam et al ., 2020; Taylor, Fien, et al, 2020; Taylor et al ., 2018). Where research is currently less clear is with regard to the efficacy of CAT.…”
Section: The Current Landscape Of Cat Researchmentioning
confidence: 99%
“…PBE also has the advantage that it better reflects real‐world practice, may better recognize individual context, and foster swift translation and implementation, which can be limited for more tightly controlled research trials (Warner & Spandler, 2012). Within this special issue, there are examples of PBE providing preliminary support for the acceptability of group CAT for anxiety and depression (Martin, Byrne, Connon, & Power, 2020), and for a hybrid CAT‐informed therapy for people who attend Emergency Departments following self‐harm (Taylor, Fien, et al, 2020). There is also an example of a more complex single‐case design (Kellett, Gausden, & Gaskell, 2020), demonstrating how practice‐based studies can provide in‐depth quantitative assessment of change in individual cases.…”
Section: The Current Landscape Of Cat Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous evaluation of this therapy approach within ED settings found that 64% of referred individuals attended at least one therapy session, with nearly half (n=26, 49%) attending all four sessions. 29 There was also evidence of a reduction in distress over the therapy period.…”
mentioning
confidence: 95%
“…COPESS is a modi ed version of psychodynamic -interpersonal therapy (PIT) which has previously been evaluated in two randomised trials for self-harm 26 and has also been used in NHS self-harm services in England. 29 PIT has undergone two modi cations for the purposes of this trial. Elements of another closely linked therapy, Cognitive Analytic Therapy (CAT), 30 have been added to the intervention with the use of visual mapping and a focus on identifying "exits" or solutions to clients' di culties.…”
mentioning
confidence: 99%